Distinct cholinergic circuits underlie discrete effects of reward on attention - Runyon, Kelly; Bui, Tung; Mazanek, Sarah; Hartle, Alec; Marschalko, Katie; Howe, William Matthew (Frontiers in Molecular Neuroscience, 2024)
Attention and reward are functions that are critical for the control of behavior, and massive multi-region neural systems have evolved to support the discrete computations associated with each. Previous research has also identified that attention and reward interact, though our understanding of the neural mechanisms that mediate this interplay is incomplete. Here, we review the basic neuroanatomy of attention, reward, and cholinergic systems. We then examine specific contexts in which attention and reward computations interact. Building on this work, we propose two discrete neural circuits whereby acetylcholine, released from cell groups located in different parts of the brain, mediates the impact of stimulus-reward associations as well as motivation on attentional control. We conclude by examining these circuits as a potential shared loci of dysfunction across diseases states associated with deficits in attention and reward.